Copper foil and preparation method thereof, circuit board and current collector

By introducing nanodomains into electrolytic copper foil and optimizing its distribution, combined with DC electrolytic deposition technology, the problem of insufficient tensile strength in the existing technology is solved, and the preparation of high-performance copper foil is realized, which meets the high-performance lithium-ion battery and Electronic circuit requirements.

CN119296850AActive Publication Date: 2025-01-10INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411383997.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

It is difficult to obtain electrolytic copper foils with higher tensile strength in the prior art, and the production of high-performance electrolytic copper foils depends on imports, resulting in a shortage of high-end electrolytic copper foils in China.

Method used

By introducing nanodomains into the microstructure of copper foil, the nanodomains are distributed inside the grain or on the grain boundary, and the density and size of the nanodomains are regulated through DC electrolytic deposition technology, combining specific additives and current density to optimize the microscope of copper foil Structure to improve tensile strength and elongation.

Benefits of technology

It achieves high tensile strength and elongation of copper foil, exceeds the existing standards, and has high thermal stability and low surface roughness, and is suitable for high performance lithium-ion batteries and electronic circuit fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296850A_ABST
    Figure CN119296850A_ABST
Patent Text Reader

Abstract

The invention provides a copper foil and a preparation method thereof, a circuit board and a current collector, and relates to the technical field of copper foil preparation, a microstructure of the copper foil contains nano domains, and the distribution state of the nano domains is one or more of the following states: the nano domains are in crystal grains, on crystal boundaries, both in the crystal grains and on the crystal boundaries. On one hand, the nano domains can effectively hinder dislocation movement, the dislocation storage capacity is improved, the strength of the copper foil is improved, and the elongation of the copper foil is contributed; and on the other hand, the nano domains can hinder grain boundary migration and ensure the stability of the grain boundary, and the stable grain boundary can refine the grains to nanometer magnitude, so that the strength of the copper foil is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper foil preparation, and in particular relates to a copper foil and a preparation method thereof, as well as a circuit board and a current collector. Background Art

[0002] Copper foil is widely used in new electronic information industry, new energy automobile industry, aerospace and other major national projects as the "neural network" for signal and power transmission and communication of electronic products and the "current collector" of lithium-ion batteries. High-performance copper foil is a key material for manufacturing high-frequency and high-speed printed circuit boards for 5G communications and high-energy-density lithium-ion batteries. However, due to the constraints on my country's copper foil production technology and the confidentiality of foreign copper foil production technology, the development of my country's copper foil production level is seriously restricted, resulting in an oversupply of medium and low-grade copper foil in my country, and a lack of high-end electrolytic copper foil production, especially high-end ultra-thin electrolytic copper foil and high-performance electrolytic copper foil, which are almost entirely dependent on imports.

[0003] Electrolytic copper foil is a key material for the manufacture of high-quality copper-clad laminates and high-quality battery negative electrode current collectors. Under the harsh circuit use environment and the high load requirement of the battery negative electrode, the copper foil should have high tensile strength and elongation to ensure efficient signal transmission when the circuit board is bent or the temperature changes sharply, and the copper foil current collector does not break or wrinkle during electrode coating and rolling. Grain refinement can effectively improve the mechanical properties of electrolytic copper foil. In the production of electrolytic copper foil, adding a small amount of additives can have a great impact on the grain size, brightness, flatness, internal stress, etc. of the coating. At present, the improvement of the strength of electrolytic copper foil is essentially achieved based on the traditional "fine grain strengthening" principle. Therefore, in the research and development of high-performance electrolytic copper foil, most electrolytic copper foil companies, in addition to the advancement of technology and equipment, are equally important to develop new, stable, and easy-to-control additives.

[0004] Reducing the grain size of electrolytic copper foil can effectively improve the yield strength, and then effectively improve the tensile strength. In the process of preparing electrolytic copper foil, by adding a certain amount of additives, the grain size is reduced from the micron level to the submicron level, and the tensile strength of the electrolytic copper foil can be increased from about 280MPa to about 400MPa. When the grain size is reduced, the resistance to dislocation movement of the electrolytic copper foil during deformation increases, thereby improving its tensile strength; at the same time, the movement space and storage capacity of the dislocation are also reduced, resulting in a decrease in its elongation (plasticity). In addition, when the grain size is reduced to the nanometer level, the grain boundaries of the electrolytic copper foil become extremely unstable, and self-annealing of grain growth can occur even at room temperature. As the storage time increases, the grain size continues to increase until it reaches stability, making it difficult to maintain the tensile strength at a high level. Therefore, it is difficult to obtain electrolytic copper foil with higher tensile strength by means of fine grain strengthening. Summary of the invention

[0005] Therefore, the present invention provides a copper foil and a preparation method thereof, as well as a circuit board and a current collector, which can solve the technical problem that it is difficult to obtain an electrolytic copper foil with higher tensile strength in the prior art.

[0006] In order to solve the above problems, the present invention provides a copper foil, wherein the microstructure of the copper foil contains nanodomains, and the distribution state of the nanodomains is one or more of the following states: inside the grains, on the grain boundaries, and both inside the grains and on the grain boundaries.

[0007] Furthermore, the grains are irregular in shape, and the ratio of the major axis to the minor axis of the grains is greater than 1 and less than or equal to 5; and / or

[0008] The crystal grains include columnar crystal grains and equiaxed crystal grains;

[0009] Wherein, the ratio of the major axis to the minor axis of the columnar grains is greater than 1.5 and less than or equal to 3;

[0010] The ratio of the major axis to the minor axis of the quasi-equiaxed grains is 1-2.

[0011] Furthermore, the size of the nanodomain is 1-50 nm; and / or

[0012] The average volume fraction of the nanodomains is greater than 0.01%;

[0013] Preferably, the nanodomains are distributed alternately in low-density areas and high-density areas; wherein the volume fraction of the nanodomains in the low-density areas is not higher than the average volume fraction, and the volume fraction of the nanodomains in the high-density areas is higher than the average volume fraction.

[0014] Furthermore, the copper foil is entirely composed of copper elements; or

[0015] The copper foil comprises copper element with a mass fraction of not less than 90% and one or more elements including carbon, oxygen, sulfur, nitrogen, chlorine, hydrogen, phosphorus, silver, nickel, iron, molybdenum, tungsten, chromium, cerium and zinc.

[0016] Furthermore, at room temperature, the copper foil has a tensile strength of 400-1000 MPa and an elongation of more than 3%; and / or

[0017] The surface roughness Rz of the copper foil is 0.1-3.0 μm; and / or

[0018] The thickness of the copper foil is 1-200 μm;

[0019] Preferably, when the copper foil has a thickness of 1-4 μm, the copper foil is used to be compounded with a carrier to form a carrier copper foil.

[0020] On the other hand, the present invention provides a method for preparing the copper foil described in any one of the above items, characterized in that the copper foil is deposited by a direct current electrolytic deposition method; wherein the electrolyte used includes additives; the additives include gelatin, polyethylene glycol, hydroxyethyl cellulose, glucose, 2-mercaptobenzimidazole, sodium polydisulfide dipropane sulfonate, and thiourea;

[0021] Preferably, the deposition method is an electrolytic cell flat plate deposition method or a foil machine roller deposition method; wherein, if the electrolytic cell flat plate deposition method is selected, the deposition time is 1-3 minutes.

[0022] Furthermore, in the additive: the concentration of gelatin is 1-40 mg / L, the concentration of polyethylene glycol is 1-20 mg / L, the concentration of hydroxyethyl cellulose is 1-10 mg / L, the concentration of glucose is 10-300 mg / L, the concentration of 2-mercaptobenzimidazole is 0.5-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 1-20 mg / L, and the concentration of thiourea is 1-15 mg / L;

[0023] Preferably, the concentration of gelatin is 5-20 mg / L, the concentration of polyethylene glycol is 1-10 mg / L, the concentration of hydroxyethyl cellulose is 1-5 mg / L, the concentration of glucose is 50-200 mg / L, the concentration of 2-mercaptobenzimidazole is 2-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 5-15 mg / L, and the concentration of thiourea is 2-8 mg / L;

[0024] Furthermore, the electrolyte also includes copper sulfate pentahydrate, sulfuric acid H2SO4, hydrochloric acid HCl and deionized water;

[0025] Among them, the concentration of copper sulfate pentahydrate is 200-350g / L, the concentration of sulfuric acid H2SO4 is 20-120g / L, and the concentration of hydrochloric acid HCl is 5-50mg / L.

[0026] Furthermore, during the DC electrolytic deposition process, the current density is 10-110A / dm 2 ; Temperature is 10-60℃;

[0027] The preferred current density is 40-70A / dm 2 ; The temperature is 30-50℃.

[0028] Furthermore, it is characterized in that the density of nanodomains, the size of nanodomains, and the average minor axis size of grains in the copper foil are regulated by adjusting the temperature of the electrolyte, the concentration of one or more components in the additive, and the current density during the direct current electrolytic deposition process; and / or

[0029] The strength of the copper foil is regulated by adjusting one or more of the density of nanodomains, the size of nanodomains, the average minor axis size of grains, the proportion of twin structures, and the thickness of twin lamellae in the copper foil; and / or

[0030] The surface roughness of the copper foil is adjusted by adjusting one or more of the density of the nanodomains, the size of the nanodomains, and the average minor axis size of the grains in the copper foil.

[0031] In another aspect, the present invention provides a circuit board, comprising a substrate and the copper foil described in any one of the above items; wherein the copper foil is located on the substrate;

[0032] Preferably, the copper foil is bonded to the substrate.

[0033] In another aspect, the present invention provides a current collector, comprising graphite and any one of the above copper foils; wherein the graphite is bonded to the copper foil;

[0034] Preferably, the current collector is used in a lithium battery.

[0035] On the other hand, the present invention provides a method for packaging an electronic circuit. During the packaging of the electronic circuit, copper foil is deposited in a blind hole of a circuit board using any of the copper foil preparation methods described above to implement the electronic circuit packaging operations of circuit board wiring and interlayer interconnection.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects:

[0037] 1. The present invention provides a copper foil, wherein nanodomains exist in the microstructure of the copper foil. On the one hand, these nanodomains can effectively hinder dislocation movement and improve dislocation storage capacity, thereby improving the strength of the copper foil and contributing to its elongation. On the other hand, these nanodomains can hinder grain boundary migration and ensure grain boundary stability. Stable grain boundaries can refine grains to the nanometer level, further improving the strength of the copper foil. For example, taking the copper foil of the embodiment of the present invention with an average nanodomain size of 3.1 nm and a volume fraction of 2% as an example, its room temperature tensile property (tensile strength) is 778 MPa and its elongation is 4.1%. Its strength far exceeds the requirements of the tensile strength (276 MPa) of the IPC-4562 copper foil standard for electronic circuit printed boards and the tensile strength (300 MPa) of the SJ / T 11483-2014 copper foil standard for lithium-ion batteries, and also fully meets the requirements of the elongation in the standard. At the same time, the nanodomain copper foil has high thermal stability. After being placed at room temperature for 3 months or baked at 150 degrees Celsius for 10 minutes, the tensile strength decays by less than 5%, overcoming the self-annealing phenomenon of conventional copper foil (tensile strength decays by more than 50% at room temperature).

[0038] 2. On the other hand, the present invention provides a method for preparing copper foil, wherein the copper foil is deposited by direct current electrolytic deposition technology; specifically, the selected additives include not only strong surfactants such as gelatin and hydroxyethyl cellulose, additives with certain reducing properties such as glucose and 2-mercaptobenzimidazole, but also additives such as sodium polydisulfide dipropane sulfonate and thiourea with strong surface adsorption capacity; the above-mentioned multi-complex system has a good synergistic effect on the copper plating layer, can produce a strong cathode polarization, and will continuously produce a high overpotential. For example, the coupling effect between the additives causes uneven adsorption. When the additives are locally adsorbed more, the overpotential in this area is higher. According to the electrocrystallization theory, the increase in overpotential will greatly promote the generation of crystal nuclei; however, some additives will be quickly consumed or desorbed, resulting in a decrease in the overpotential in this area, and the crystal nuclei cannot continue to grow, so a nano-domain with extremely small size is formed. When the adsorption and consumption (or desorption) of the additives change periodically, a periodic distribution of nano-domains will be formed.

[0039] 3. Furthermore, the method for preparing the copper foil provided by the present invention has strong controllability and is easy to optimize performance. Here, the size of the nanodomains in the copper foil, the volume fraction of the nanodomains, the grain size (average minor axis size), etc. can be adjusted by changing the current density, the concentration of each component of the additive, the temperature and other parameters, so as to further optimize the performance of the copper foil. Taking Example 1-2 of the present invention as an example, when the current density is increased from 65A / dm 2 Increased to 80A / dm 2 The average volume fraction of nanodomains increased from 2.3% to 3.7%, which increased the tensile strength of the copper foil from 701MPa to 883MPa, the elongation at break from 1.8% to 3.0%, and the surface roughness Rz from 0.98μm to 0.32μm.

[0040] 4. In addition, by changing the current density and the concentration of the additive, the distribution of the nanodomains in the copper foil of the present invention can be effectively controlled, and not only random distribution but also periodic distribution (i.e., the nanodomains are distributed in the grains in alternating intervals of low-density areas and high-density areas) can be achieved. Compared with randomly distributed nanodomains, high-density nanodomains in periodically distributed nanodomains can contribute higher strength, and low-density nanodomains can contribute higher elongation, so periodically distributed nanodomains can combine the advantages of both. In addition, the different strengths of the two will cause incoordination in deformation, further generating geometrically necessary dislocations, which further enhances work hardening and improves strength and plasticity at the same time.

[0041] In summary, the copper foil and preparation method thereof provided by the present invention enable the copper foil to have the advantages of extremely high strength, high elongation, high stability, extremely low surface roughness and extremely thin thickness, etc., which greatly meet the current development of electronic products towards miniaturization, lightweight, thinness, multi-function and high reliability, the high performance requirements of thin multi-layer printed circuit boards and thin double-sided cloth-based copper-clad laminates, and the development needs of high-performance lithium-ion batteries and electronic circuits with high safety, high stability, high energy density and low cost, and therefore have huge application prospects in the fields of new energy batteries and electronic circuits. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0043] Figure 1 Schematic diagram of nanodomain distribution of nanodomain copper foil;

[0044] Figure 2 Figure 1 is a transmission electron microscope image of a cross section of the copper foil in Example 1, wherein Figure A is a TEM bright field image of the cross section of the copper foil, Figure B is a high-magnification HRTEM image of the nanodomains in the grains, and Figures C, D, and E are EELS distributions of C, O, and Cl elements in the nanodomains, respectively;

[0045] Figure 3 This is a bright field transmission electron microscope image of the cross section of the copper foil in Example 2;

[0046] Figure 4 4A and 4B are electron microscope images of the cross section of the copper foil in Example 3, wherein 4A and 4B are scanning electron microscope images and transmission electron microscope images, respectively;

[0047] Figure 5 1-3 are the tensile engineering stress-strain curves of the copper foil samples in Examples 1-3. DETAILED DESCRIPTION

[0048] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0049] The invention provides a copper foil, wherein the microstructure of the copper foil contains nano domains; the distribution state of the nano domains is one or more of the following states: inside the crystal grains, on the crystal boundaries, or both inside the crystal grains and on the crystal boundaries.

[0050] The term "nanodomain" as used in this application refers to a nanoscale tiny area distributed on a (matrix) grain, the crystal structure and / or composition of which is different from that of the (matrix) grain; specifically, the average angle difference between the (111) plane of the region below the (110) crystal zone axis and the (111) plane of the (matrix) grain is 0-15°; compared with the matrix grain, there is a small amount of enrichment of elements such as C and O in the nanodomain (see Figure 2 ); wherein the nanodomain size is 1-50 nm, which is smaller than the (matrix) grain size; there is an interface between the nanodomain and the (matrix) grain, and there is an interface (i.e., grain boundary) between the (matrix) grains.

[0051] Nanodomains can be randomly distributed or periodically distributed (see Figure 1 ). Periodic distribution refers to the volume fraction of nanodomains being distributed alternately from high-density areas to low-density areas along the thickness direction of the copper foil, and presenting at least one periodic distribution, that is, being distributed alternately in low-density areas and high-density areas. In the present application, the (overall) average volume fraction of nanodomains is greater than 0.01%; wherein, the volume fraction of nanodomains in the low-density area is not higher than the average volume fraction, and the volume fraction of nanodomains in the high-density area is higher than the average volume fraction. Compared with randomly distributed nanodomains, periodically distributed nanodomains give the copper foil higher tensile strength and elongation. Among them, high-density nanodomains can contribute higher strength, and low-density nanodomains can contribute higher elongation, so periodically distributed nanodomains can combine the advantages of both.

[0052] Preferably, the grains are irregular in shape, and the ratio of the major axis to the minor axis of the grains is greater than 1 and less than or equal to 5; preferably 1.5-3; the grains include columnar grains and equiaxed grains;

[0053] Among them, the ratio of the major axis to the minor axis of the columnar grains is greater than 1.5 and less than or equal to 3;

[0054] The ratio of the major axis to the minor axis of quasi-equiaxed grains is 1-2.

[0055] Furthermore, the grains also include twin structures; and / or

[0056] Furthermore, at room temperature, the tensile strength of the copper foil is 400-1000 MPa, and the elongation is higher than 3%; the surface roughness Rz of the copper foil is 0.1-3.0 μm; and the thickness of the copper foil is 1-200 μm;

[0057] Preferably, when the thickness of the copper foil is 1-4 μm, the copper foil is used to be compounded with a carrier to form a carrier copper foil; preferably, the thickness of the carrier is 6-30 μm; preferably, the carrier is selected from one of copper foil, aluminum foil, and organic film.

[0058] Among them, the composition of the copper foil is entirely composed of copper elements; or the composition of the copper foil includes copper elements with a mass fraction of not less than 90%; and further includes one or more elements of carbon, oxygen, sulfur, nitrogen, chlorine, hydrogen, phosphorus, silver, nickel, iron, molybdenum, tungsten, chromium, cerium, and zinc. In addition to these elements actively added, it is also affected by the purity of the solution and additives. When composed of multiple elements, these elements can play a role in solid solution strengthening, thereby improving the strength of the copper foil.

[0059] On the other hand, the present invention provides a method for preparing the copper foil described in any one of the above items, characterized in that the copper foil is deposited by a direct current electrolytic deposition method; wherein the electrolyte used comprises additives, copper sulfate pentahydrate, sulfuric acid H2SO4, hydrochloric acid HCl and deionized water; the additives comprise gelatin, polyethylene glycol, hydroxyethyl cellulose, glucose, 2-mercaptobenzimidazole, sodium polydisulfide dipropane sulfonate, and thiourea;

[0060] Preferably, the deposition method is an electrolytic cell flat plate deposition method or a foil machine roller deposition method; wherein, if the electrolytic cell flat plate deposition method is selected, the deposition time is 1-3 minutes.

[0061] During the DC electrolytic deposition process, the current density is 10-110A / dm 2 ; Temperature is 10-60℃;

[0062] Preferably, the current density is 40-70A / dm 2 ; The temperature is 30-50℃.

[0063] In the additives: the concentration of gelatin is 1-40 mg / L, the concentration of polyethylene glycol is 1-20 mg / L, the concentration of hydroxyethyl cellulose is 1-10 mg / L, the concentration of glucose is 10-300 mg / L, the concentration of 2-mercaptobenzimidazole is 0.5-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 1-20 mg / L, and the concentration of thiourea is 1-15 mg / L;

[0064] Preferably, the concentration of gelatin is 5-20 mg / L, the concentration of polyethylene glycol is 1-10 mg / L, the concentration of hydroxyethyl cellulose is 1-5 mg / L, the concentration of glucose is 50-200 mg / L, the concentration of 2-mercaptobenzimidazole is 2-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 5-15 mg / L, and the concentration of thiourea is 2-8 mg / L;

[0065] Among them, the concentration of copper sulfate pentahydrate is 200-350g / L, the concentration of sulfuric acid H2SO4 is 20-120g / L, and the concentration of hydrochloric acid HCl is 5-50mg / L.

[0066] Further, the density of nanodomains, the size of nanodomains, and the average minor axis size of grains in the copper foil are regulated by adjusting the temperature of the electrolyte, the concentration of one or more components in the additive, and the current density during the direct current electrolytic deposition process; and / or

[0067] The strength of the copper foil is regulated by adjusting one or more of the density of nanodomains, the size of nanodomains, the average minor axis size of grains, the proportion of twin structures, and the thickness of twin lamellae in the copper foil; and / or

[0068] The surface roughness of the copper foil can be adjusted by adjusting one or more of the density of nanodomains, the size of nanodomains, and the average minor axis size of grains in the copper foil.

[0069] Preferably, when the nanodomain size is 1-10 nm and the nanodomain density is 1-15%, the strength of the copper foil is 500-900 MPa;

[0070] Preferably, when the average minor axis size of the grains is 10 nm-5 μm, the strength of the copper foil is 500-900 MPa;

[0071] Preferably, during the direct current electrolytic deposition process, by regulating any one of the temperature, current density, and additive concentration or regulating several of them simultaneously, the prepared copper foil can meet the following requirements: the size of the nanodomain is 1nm-30nm, the spacing of the nanodomain is 1nm-50nm, the average minor axis size of the grain is 10nm-5μm, and the strength of the copper foil is 300-900MPa; further preferably, the temperature is regulated at 20-55°C; the current density is regulated at 40-100A / dm 2 ; The concentrations of the additives are regulated as follows: the concentration of gelatin is 5-20 mg / L, the concentration of polyethylene glycol is 1-10 mg / L, the concentration of hydroxyethyl cellulose is 1-5 mg / L, the concentration of glucose is 50-200 mg / L, the concentration of 2-mercaptobenzimidazole is 2-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 5-15 mg / L, and the concentration of thiourea is 2-8 mg / L;

[0072] It should be noted that the size, spacing, volume fraction of nanodomains and average minor axis size of grains can be reduced by adjusting temperature, current density and additives alone or by adjusting two or three parameters simultaneously.

[0073] In another aspect, the present invention provides a circuit board, comprising a substrate and any one of the above copper foils; wherein the copper foil is located on the substrate;

[0074] Preferably, the copper foil is bonded to the substrate.

[0075] In another aspect, the present invention provides a current collector, comprising graphite and any one of the above copper foils; wherein the graphite is bonded to the copper foil;

[0076] Preferably, the current collector is used in a lithium battery.

[0077] On the other hand, the present invention provides a method for packaging an electronic circuit. During the packaging of the electronic circuit, copper foil is deposited in a blind hole of a circuit board using any of the copper foil preparation methods described above to implement the electronic circuit packaging operations of circuit board wiring and interlayer interconnection.

[0078] The present invention is further described below with reference to specific embodiments and comparative examples.

[0079] Example 1

[0080] This embodiment provides a copper foil, wherein the nanodomains are randomly distributed, and is specifically prepared by direct current electrolytic deposition technology, wherein:

[0081] The electrolytic deposition equipment is a DC voltage and current stabilized power supply; the anode and cathode are iridium tantalum titanium plate and pure titanium plate respectively;

[0082] Requirements for the electrolyte used for electrolytic deposition: Use analytical pure copper sulfate pentahydrate and pure water to prepare a copper sulfate solution with a concentration of about 300g / L, then add analytical pure concentrated sulfuric acid to make the concentration of H2SO4 100g / L, add HCL to make the concentration of HCl 15mg / L, and form a basic solution for electrolytic deposition. Then add additives, specifically, the concentration of gelatin is 8mg / L, the concentration of polyethylene glycol is 4mg / L, the concentration of hydroxyethyl cellulose is 6mg / L, the concentration of glucose is 100mg / L, the concentration of 2-mercaptobenzimidazole is 3mg / L, the concentration of polydisulfide dipropane sulfonate is 1mg / L, and the concentration of thiourea is 3mg / L;

[0083] Electrolytic deposition process parameters: DC electrolysis is used to electroplate copper foil, where the current density is 65A / dm 2 The cathode and anode are placed in parallel with a spacing of 15 mm, and the area ratio of the cathode and anode is 1:1; the electrolysis temperature is 53 ° C; a water pump is used for electrolyte circulation, and the water pump power is 2.2m 3 / h; preparation time (deposition time) is 70 seconds.

[0084] The area of ​​the copper foil prepared in this embodiment is 180×70 mm 2 The thickness was measured by weighing method and was 9.0 μm.

[0085] Figure 2This is a bright field image of the cross section of the copper foil prepared in this embodiment under a transmission electron microscope. The transmission electron microscope test shows that the copper foil prepared in this embodiment is composed of nano-grains, which are irregular in shape, with a ratio of the major axis to the minor axis between 1 and 4.5, an average of 2.8, and an average minor axis grain size of 77nm; twin boundaries are randomly distributed inside some grains, and the thickness of the twin lamellae is less than 100 nanometers, and the twin lamellae are parallel to the major axis direction of the grains; nano-domains are randomly distributed inside the grains and on the grain boundaries, with an average size of about 3.4nm and an average volume fraction of about 2.3%. The transmission electron microscope EELS component analysis shows that there are more C elements in the nano-domains than in the matrix. More C elements can play a role in solid solution strengthening.

[0086] The copper foil prepared in this embodiment has high strength, can be smoothly and completely peeled off from the titanium plate, and has no pinholes or burrs.

[0087] The room temperature stretching results of the copper foil prepared in this example are as follows: Figure 5 The test conditions are as follows: the tensile test sample is cut by a JDC-0.5-10 precision cutter, with a length × width of 50 mm × 12 mm, and the tensile performance is tested by a tensile testing machine Instron 5848, with a tensile rate of 50 mm / min. The test results show that the tensile strength of the nano-twin copper foil prepared in this embodiment is 701 MPa and the elongation at break is 1.8%.

[0088] Example 2

[0089] This embodiment provides a copper foil, which is specifically prepared by direct current electrolytic deposition technology. The difference from Example 1 is that during direct current electrolytic deposition, the current density is increased, and the concentration of each additive and the time of electrolytic deposition are adjusted; the specific direct current electrolytic deposition parameters are as follows:

[0090] The electrolytic deposition equipment is a DC voltage and current stabilized power supply; the anode and cathode are iridium tantalum titanium plate and pure titanium plate respectively;

[0091] Requirements for the electrolyte used for electrolytic deposition: Analytical pure copper sulfate pentahydrate and pure water are used to prepare a copper sulfate solution with a concentration of about 300 g / L, and then analytical pure concentrated sulfuric acid is added to make the concentration of H2SO4 100 g / L, and HCL is added to make the concentration of HCl 15 mg / L to form a basic solution for electrolytic deposition. Additives are then added, specifically, the concentration of gelatin is 10 mg / L, the concentration of polyethylene glycol is 6 mg / L, the concentration of hydroxyethyl cellulose is 3 mg / L, the concentration of glucose is 150 mg / L, the concentration of 2-mercaptobenzimidazole is 2.5 mg / L, the concentration of polydisulfide dipropane sulfonate sodium is 5 mg / L, and the concentration of thiourea is 3 mg / L.

[0092] Electrolytic deposition process parameters: DC electrolysis is used to electroplate copper foil, where the current density is 70A / dm 2 The cathode and anode are placed in parallel with a spacing of 15 mm, and the area ratio of the cathode and anode is 1:1; the electrolysis temperature is 53 ° C; a water pump is used for electrolyte circulation, and the water pump power is 2.2m 3 / h; preparation time (deposition time) is 60 seconds.

[0093] The thickness of the copper foil in this embodiment was measured by weighing method and was 9.8 μm.

[0094] Figure 3 The cross-sectional bright field images of the copper foil prepared in this embodiment under a transmission electron microscope are shown respectively. It shows that most of the grains in the microstructure of the copper foil are slender columnar crystals, the ratio of the major axis to the minor axis is between 1-4, the average value is 2.7, and the average minor axis grain size is 60nm; it can be seen that the nanodomains are distributed periodically, that is, they are distributed alternately in low-density areas and high-density areas. Columnar crystals can grow across nanodomains; the average size of the nanodomains is about 3nm, and the (overall) average volume fraction of the nanodomains in the copper foil is about 3.7%; the nanodomains in the copper foil prepared in this embodiment are distributed periodically, wherein the volume fraction of the nanodomains in the low-density area is about 1.2%, and the volume fraction of the nanodomains in the high-density area is about 7.2%.

[0095] Compared with Example 1, this example adjusts the current density and the concentration parameters of each additive so that the nanodomains in the copper foil prepared in this example present a periodic distribution of high-density areas and low-density areas, the average spacing of the nanodomains is about 5.8nm, and the average volume fraction is increased to 3.7%.

[0096] The average minor axis size of the grains of the copper foil prepared in this embodiment is reduced to 60nm, and the grain size has a slight increasing trend along the thickness direction of the copper foil, the average minor axis size of the grains near the lower surface (glossy surface) is 125nm; the average minor axis size of the grains near the upper surface (rough surface) is 172nm. In the copper foil prepared in this embodiment, twin boundaries exist in some grains.

[0097] Compared with Example 1, this example achieves the reduction of the spacing between nanodomains, grain size (average minor axis size of grains) and volume fraction of nanodomains by actively regulating the current density and the concentration of each additive, and the roughness of the matte surface of the copper foil is reduced to Rz=0.32μm and Ra=0.14μm.

[0098] The room temperature tensile test results of the copper foil prepared in this embodiment are as follows: Figure 5As shown. Compared with Example 1, the present invention reduces the spacing between nanodomains, the grain size and the density of nanodomains by actively regulating the current density and the concentration of each additive, so that the tensile strength of the copper foil is increased to 883MPa and the elongation is 3.0%. Moreover, after the copper foil of this embodiment is aged at room temperature for one year, the tensile strength and elongation remain basically unchanged (the change rate is less than 5%), which shows that the copper foil prepared in this embodiment has high room temperature stability.

[0099] Example 3

[0100] This embodiment provides a copper foil, wherein nanodomains are randomly distributed in the grains, and is specifically prepared by using a direct current electrolytic deposition technology. The difference from Embodiment 1 is that during direct current electrolytic deposition, the current density is increased, and the concentration of each additive and the time of electrolytic deposition are adjusted; the specific direct current electrolytic deposition parameters are as follows:

[0101] The electrolytic deposition equipment is a DC voltage and current stabilized power supply; the anode and cathode are iridium tantalum titanium plate and pure titanium plate respectively;

[0102] Requirements for the electrolyte used for electrolytic deposition: Analytical pure copper sulfate pentahydrate and pure water are used to prepare a copper sulfate solution with a concentration of about 300 g / L, and then analytical pure concentrated sulfuric acid is added to make the concentration of H2SO4 100 g / L, and HCL is added to make the concentration of HCl 15 mg / L to form a basic solution for electrolytic deposition. Additives are then added, specifically, the concentration of gelatin is 16 mg / L, the concentration of polyethylene glycol is 8 mg / L, the concentration of hydroxyethyl cellulose is 2 mg / L, the concentration of glucose is 250 mg / L, the concentration of 2-mercaptobenzimidazole is 3 mg / L, the concentration of polydisulfide dipropane sulfonate is 8 mg / L, and the concentration of thiourea is 6 mg / L.

[0103] Electrolytic deposition process parameters: DC electrolysis is used to electroplate copper foil, where the current density is 80A / dm 2 The cathode and anode are placed in parallel with a spacing of 15 mm, and the area ratio of the cathode and anode is 1:1; the electrolysis temperature is 53 ° C; a water pump is used for electrolyte circulation, and the water pump power is 2.2m 3 / h; preparation time (deposition time) is 55 seconds.

[0104] The thickness of the copper foil in this embodiment was measured by weighing method and found to be 10.2 μm.

[0105] The copper foil prepared in this embodiment was tested using a scanning electron microscope and a transmission electron microscope. Figure 4As shown, the copper foil prepared in this embodiment undergoes self-annealing behavior, most of the grains are equiaxed grains, the grain size is significantly increased to about 3.8μm, and some cross-sectional grains grow to run through the entire thickness direction of the copper foil; at the same time, there are a large number of annealing twins, and the twin layer thickness is about 62nm and the length is about 766nm; nanodomains grow inside the grains, and the average size of the nanodomains grows slightly to about 4.5nm, and the volume fraction of the nanodomains accounts for about 3.6%.

[0106] Compared with Example 1, this embodiment adjusts the process parameters so that the grain size of the copper foil grows, the nanodomains in the grains grow slightly, and the proportion of twin boundaries and the volume share are significantly increased. The thickness of the annealed twin layer is about 62nm and 86nm, and the volume share is about 42% and 18%.

[0107] Compared with Example 1, in this example, the current density and the concentration of each additive in the electrolyte are actively regulated, and the roughness of the matte surface of the copper foil is Rz=0.5 μm and Ra=0.12 μm.

[0108] The room temperature tensile test results of the copper foil prepared in this embodiment are as follows: Figure 5 Compared with Example 1, this embodiment significantly increases the grain size and twin density and slightly increases the nanodomain size by actively regulating the current density and the concentration of each additive, so that the tensile strength of the copper foil of this embodiment is 545 MPa and the elongation at break is increased to 5.0%.

[0109] The mechanical property requirements of the printed circuit board metal foil standard IPC-4562 for standard electrolytic copper foil with a thickness of 17μm include: tensile strength ≥207MPa, elongation ≥2%; for 17μm thick rolled forged copper foil, when the tensile strength is ≥345MPa, the elongation is ≥0.5%.

[0110] The copper foil prepared in the embodiment of the present invention is not only thinner but also has higher elongation and lower surface roughness. This is because the grain size of the nanodomain copper foil is small and nanodomains grow inside the grains.

[0111] The requirements of the electrolytic copper foil industry standard SJ / T 11483-2014 for electrolytic copper foil for lithium-ion batteries include: LBEC-01 model, when the thickness is 8-20μm, measured at room temperature (23℃), the tensile strength is ≥294MPa, the elongation is ≥3%, and the roughness of the rough surface is Rz≤3.0μm; LBEC-02, when the thickness is 8μm, 9μm, 10μm and 12μm, measured at room temperature (23℃), the tensile strength is ≥300MPa, the elongation is ≥2.5%, and the roughness of the rough surface is Rz≤3.0μm, 4.0μm, 4.5 μm and 5.0μm; for LBEC-03 model, when the thickness is 9μm, 10μm, 12μm, measured at room temperature (23℃), the tensile strength is ≥300MPa, the elongation is ≥2.5%, and the roughness of the rough surface is Rz≤4.0μm, 4.5μm and 5.0μm; for LBEC-04 model, when the thickness is 10μm, 12μm, measured at room temperature (23℃), the tensile strength is ≥300MPa, the elongation is ≥2.5%, and the roughness of the rough surface is Rz≤5.0μm, 6.0μm.

[0112] By comparison, it is found that the tensile strength of the copper foil prepared in the embodiment of the present invention is much higher than the requirements of the electrolytic copper foil standards IPC-4562 and SJ / T11483-2014.

[0113] The embodiment of the present invention adopts the electrolytic copper foil deposition equipment independently developed. With different additive ratios and current density, its thickness, strength, elongation, surface roughness, etc. greatly meet the industry standards of lithium battery electrolytic copper foil. The technical scheme of the present invention can control the microstructure parameters such as the grain size of the copper foil, the proportion of nanodomains, and the size of nanodomains by actively regulating process parameters such as current density, additive concentration, and temperature, thereby further optimizing the mechanical properties and surface roughness of the copper foil, and providing technical support for the preparation of copper foil with different performance requirements.

[0114] Comparative Example 1

[0115] Ding Jie et al. (Master's thesis of Nanchang University, 2022) used high current density to study electrolytic copper foil. The specific process parameters are: current density 70A / dm 2 , Cu 2+The concentration is 80g / L, the chloride ion concentration is 30mg / L, the sulfuric acid concentration is 110g / L, the electrodeposition temperature is 53°C, and no additives are used. The thickness of the prepared copper foil is 8μm. Without any additives, the grains on the rough surface of the copper foil are coarse, grow in blocks, and the size of the grains is very uneven. The grains are not dense, and its tensile strength is about 161MPa, the elongation is about 1.77%, the roughness of the rough surface Ra=0.51μm, and the roughness of the smooth surface Ra=0.4μm. Comparative Example 1 does not use any additives, so that the reduction process of copper ions cannot be hindered or the resistance is small, the cathode polarization degree is low, resulting in a low overpotential, and the nucleation density of the coating is reduced, which is not conducive to surface flatness and grain refinement, so nanodomains cannot be formed in the grains, so the tensile strength is low.

[0116] Comparative Example 2

[0117] He Tieshuai et al. (Shandong Industrial Technology 2020, No. 6) used hydroxyethyl cellulose, collagen, 3-mercapto-1-propanesulfonic acid inner salt, saccharin sodium, polyethylene glycol, polyoxyethylene alkyl ether and other additives to produce ultra-thin high-safety lithium battery copper foil, and the tensile strength of the produced copper foil was about 550MPa and the elongation was about 4%. In Comparative Example 2, due to the lack of reducing additives such as glucose and 2-mercaptobenzimidazole, the synergistic effect was reduced, the degree of cathode polarization was reduced, the overpotential of the entire solution system was reduced, nanodomains could not be formed, and it was difficult to stabilize the grains, so the tensile strength obtained was limited.

[0118] At the same time, the copper foil prepared by the embodiment of the present invention is not only thinner in thickness but also has higher elongation and lower surface roughness, because the grain size of the copper foil with nano-domains is small, and nano-domains grow randomly inside the grains, and there is a high-density interface. The copper foil prepared by the embodiment of the present invention is suitable for the collector of the battery, and its significant tensile strength, elongation and surface roughness and other performance advantages are in line with the development trend of high-performance lithium-ion batteries with high capacity, high safety, high stability and low cost. The smaller the thickness of the lithium battery copper foil, the lighter the weight of the battery will be. At the same time, thinner lithium battery copper foil also means smaller resistance, and the performance of the battery will also be improved. Therefore, reducing the mass of the copper foil on the battery, reducing the cost of copper foil raw materials, and providing higher energy density have become the key to copper foil for power lithium batteries. At the same time. In addition, thanks to the higher fatigue resistance, conductivity (up to 93% IACS), higher thermal stability, excellent anti-electromigration ability and weldability, the copper foil with nano-domains of the present invention and its preparation method are also suitable for circuit board manufacturing and electronic circuit packaging. In addition, the mechanical properties and surface roughness of the copper foil prepared by the embodiment of the present invention vary widely, making the copper foil have a wide range of uses. It is worth noting that the technical invention can also actively control the increase or decrease of process parameters such as current density, rotation speed, temperature, etc. to reduce or increase the size of the copper foil grains, the spacing of nanodomains, the size of nanodomains, increase or decrease the volume fraction of nanodomains, and other microstructural parameters, such as increasing the current density to 80-100A / dm 2 , the average grain size of the copper foil is refined to below 50nm, the average size of the nanodomain will also slightly decrease with the grain size and its volume fraction will increase significantly, so that copper foil with excellent surface quality can be obtained, and the mechanical properties of the copper foil can be further optimized, providing technical support for the preparation and manufacture of copper foil with different performance requirements. Therefore, it has great application potential and commercial value.

[0119] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A copper foil, characterized in that: The microstructure of the copper foil contains nano-domains, and the distribution state of the nano-domains is one or more of the following states: inside the grains, on the grain boundaries, and both inside the grains and on the grain boundaries.

2. The copper foil according to claim 1, characterized in that The crystal grains are irregular in shape, and the ratio of the major axis to the minor axis of the crystal grains is greater than 1 and less than or equal to 5; and / or The crystal grains include columnar crystal grains and equiaxed crystal grains; Wherein, the ratio of the major axis to the minor axis of the columnar grains is greater than 1.5 and less than or equal to 3; The ratio of the major axis to the minor axis of the quasi-equiaxed grains is 1-2.

3. The copper foil according to claim 1, characterized in that The size of the nanodomains is 1-50 nm; and / or The average volume fraction of the nanodomains is greater than 0.01%; Preferably, the nanodomains are distributed alternately in low-density areas and high-density areas; wherein the volume fraction of the nanodomains in the low-density areas is not higher than the average volume fraction, and the volume fraction of the nanodomains in the high-density areas is higher than the average volume fraction.

4. The copper foil according to claim 1, characterized in that The copper foil is entirely composed of copper elements; or The copper foil comprises copper element with a mass fraction of not less than 90% and one or more elements including carbon, oxygen, sulfur, nitrogen, chlorine, hydrogen, phosphorus, silver, nickel, iron, molybdenum, tungsten, chromium, cerium and zinc.

5. The copper foil according to any one of claims 1 to 4, characterized in that: At room temperature, the copper foil has a tensile strength of 400-1000 MPa and an elongation of more than 3%; and / or The surface roughness Rz of the copper foil is 0.1-3.0 μm; and / or The thickness of the copper foil is 1-200 μm; Preferably, when the copper foil has a thickness of 1-4 μm, the copper foil is used to be compounded with a carrier to form a carrier copper foil.

6. A method for preparing the copper foil according to any one of claims 1 to 5, characterized in that: The copper foil is deposited by direct current electrolytic deposition; wherein the electrolyte used includes additives; the additives include gelatin, polyethylene glycol, hydroxyethyl cellulose, glucose, 2-mercaptobenzimidazole, sodium polydisulfide dipropane sulfonate, and thiourea; Preferably, the deposition method is an electrolytic cell flat plate deposition method or a foil machine roller deposition method; wherein, if the electrolytic cell flat plate deposition method is selected, the deposition time is 1-3 minutes.

7. The method for preparing copper foil according to claim 6, characterized in that: In the additive, the concentration of gelatin is 1-40 mg / L, the concentration of polyethylene glycol is 1-20 mg / L, the concentration of hydroxyethyl cellulose is 1-10 mg / L, the concentration of glucose is 10-300 mg / L, the concentration of 2-mercaptobenzimidazole is 0.5-5 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 1-20 mg / L, and the concentration of thiourea is 1-15 mg / L; Preferably, the concentration of gelatin is 5-20 mg / L, the concentration of polyethylene glycol is 1-10 mg / L, the concentration of hydroxyethyl cellulose is 1-5 mg / L, the concentration of glucose is 50-200 mg / L, the concentration of 2-mercaptobenzimidazole is 2-5 mg / L, the concentration of sodium polydisulfide propane sulfonate is 5-15 mg / L, and the concentration of thiourea is 2-8 mg / L.

8. The method for preparing copper foil according to claim 6 or 7, characterized in that: The electrolyte also includes copper sulfate pentahydrate, sulfuric acid H2SO4, hydrochloric acid HCl and deionized water; Among them, the concentration of copper sulfate pentahydrate is 200-350g / L, the concentration of sulfuric acid H2SO4 is 20-120g / L, and the concentration of hydrochloric acid HCl is 5-50mg / L.

9. The method for preparing the copper foil according to any one of claims 6 to 8, characterized in that: During the DC electrolytic deposition process, the current density is 10-110A / dm 2 ; Temperature is 10-60℃; The preferred current density is 40-70A / dm 2 ; The temperature is 30-50℃.

10. The method for preparing the copper foil according to any one of claims 6 to 9, characterized in that: The density of nanodomains, the size of nanodomains, and the average minor axis size of grains in the copper foil are regulated by adjusting the temperature of the electrolyte, the concentration of one or more components in the additive, and the current density during the direct current electrolytic deposition process; and / or The strength of the copper foil is regulated by adjusting one or more of the density of nanodomains, the size of nanodomains, the average minor axis size of grains, the proportion of twin structures, and the thickness of twin lamellae in the copper foil; and / or The surface roughness of the copper foil is adjusted by adjusting one or more of the density of the nanodomains, the size of the nanodomains, and the average minor axis size of the grains in the copper foil.

11. A circuit board, characterized in that: The circuit board comprises a substrate and the copper foil according to any one of claims 1 to 5; wherein the copper foil is located on the substrate; Preferably, the copper foil is bonded to the substrate.

12. A current collector, characterized in that: The current collector comprises graphite and the copper foil according to any one of claims 1 to 5; wherein the graphite is bonded to the copper foil; Preferably, the current collector is used in a lithium battery.

13. A method for packaging an electronic circuit, characterized in that: During electronic circuit packaging, the copper foil preparation method according to any one of claims 6 to 10 is used to deposit copper foil in blind holes of a circuit board to achieve electronic circuit packaging operations of circuit board wiring and interlayer interconnection.

Citation Information

Patent Citations

  • Electrolytic foil, electrical component containing electrolyte foil and battery

    CN105986288A

  • Separator for secondary battery and lithium secondary battery using the same

    JP2011060539A

  • Copper foil, negative pole electrode of secondary battery, secondary battery, and printed circuit board

    JP2013151730A

  • Electrolytic copper foil, and electrical component and battery comprising the same

    JP2016160503A

  • Copper foil, preparation method therefor and use thereof

    WO2024124374A1